2014
DOI: 10.1002/cssc.201402169
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Manganese Oxides as Highly Active Water Oxidation Catalysts: A Boost from Manganese Precursor Chemistry

Abstract: We present a facile synthesis of bioinspired manganese oxides for chemical and photocatalytic water oxidation, starting from a reliable and versatile manganese(II) oxalate single-source precursor (SSP) accessible through an inverse micellar molecular approach. Strikingly, thermal decomposition of the latter precursor in various environments (air, nitrogen, and vacuum) led to the three different mineral phases of bixbyite (Mn2 O3 ), hausmannite (Mn3 O4 ), and manganosite (MnO). Initial chemical water oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 109 publications
5
99
0
1
Order By: Relevance
“….T he spectrumi sv ery similar to that reportedb yD riess and coworkers. [22] The peaks at 600 and 480 cm À1 most likely correspond to the coupled stretching modes MnÀOb onds located in tetrahedral and octahedral sites, [23] thesepeaks are slightly red-shift- [23] The broad and narrow absorption bands at 3400 and 1650 cm À1 correspond to the OÀHs tretching and bending modes of adsorbed water,r espectively.S ome minor CÀOr elated vibration modes were found at 1431a nd 1546 cm…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“….T he spectrumi sv ery similar to that reportedb yD riess and coworkers. [22] The peaks at 600 and 480 cm À1 most likely correspond to the coupled stretching modes MnÀOb onds located in tetrahedral and octahedral sites, [23] thesepeaks are slightly red-shift- [23] The broad and narrow absorption bands at 3400 and 1650 cm À1 correspond to the OÀHs tretching and bending modes of adsorbed water,r espectively.S ome minor CÀOr elated vibration modes were found at 1431a nd 1546 cm…”
Section: Resultsmentioning
confidence: 99%
“…The high-resolution TEM analysis and FTIR spectra (Figure 4b-e, c c)f urther support the formation of pure Mn 2 O 3 and al arge increasei np rimary particle diameter.T he presence of three peaks at approximately 478, 562,a nd 653 cm À1 ,a nd three smaller shoulders are comparable to those reported by Driess and coworkers. [22] These bands are attributed to surface and bulk MnÀOv ibrational modes.T heir position, and relative intensity depend on particle size and lattice disorder as observed by Chen et al…”
mentioning
confidence: 99%
“…Small peaks associated with Mn 3 O 4 can also be observed. It has been reported that formation of amorphous MnO X and Mn 3 O 4 phases leads to an increase of specific surface area [43]; this was observed with the reactivated catalyst whose specific area was enhanced from 28 to 60 m 2 g −1 . These changes did not significantly modify the performance in hydrogenolysis of 1.0 wt % of xylitol in water with a molar ratio xylitol/Ru of 77, as shown in Table 3.…”
Section: Influence Of Operating Conditionsmentioning
confidence: 69%
“…Small peaks associated with Mn3O4 can also be observed. It has been reported that formation of amorphous MnOX and Mn3O4 phases leads to an increase of specific surface area [43]; this was After the first run, the used Ru-(Mn-Al)O X catalyst was washed with distillated water and reduced at 450 • C for 3 h in order to eliminate the surface hydroxyls and to reactivate Ru. The XRD analysis of the reactivated catalyst in Figure 7 shows that MnO was again the main crystalline phase.…”
Section: Influence Of Operating Conditionsmentioning
confidence: 99%
“…Recently, we were intensively involved in exploring different synthetic strategies to develop water oxidation catalysts based on transition metal oxides [59][60][61][62]. Partial oxidation of the crystalline cubic MnO nanoparticles with Ce IV to amorphous mixed valent MnO x led to the formation of efficient catalysts for the chemical, photochemical and electrochemical water oxidation [60].…”
Section: Introductionmentioning
confidence: 99%